Validating the Efficiency of the AquaCrop Model Under Full and Deficit Irrigation Regimes to Simulate Future Climate Impacts on Wheat Crop - Shamim Ara Memon; Irfan Ahmed Shaikh; Mashooque Ali Talpur; Abdul Rahim Junejo; Munir Ahmed Mangrio; Nazar Gul; Zaheer Ahmed Khan; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2026)
Wheat yield and water demand are affected by the ongoing disturbance of climatic factors and greenhouse gases (GHG). As a result, the AquaCrop model's ability to anticipate climate change impacts on wheat harvests under full and deficit irrigation regimes in Sindh, Pakistan, was evaluated using wheat trials conducted between 2018 and 2020. However, for its validation, the results of the deficit irrigation treatment ITS 50 (50% controlled irrigation at the tillering stage) for both seasons were employed. The model efficiently estimated yield with a normalised root‐mean‐square error (NRMSE) of 13% and 17%, a Willmott's d ‐index of 98% and a Nash–Sutcliffe efficiency (NME) of 95% under full and deficit irrigation treatments, respectively. The simulation results revealed an adverse effect of climate change on the yield and water productivity of wheat. Over the century, the model predicted an increase of 6% to 7% in wheat yield under full (well‐watered) irrigation and a decrease of 10 to 12% in 25% reduced water applied depth (RAD) and 21% to 24% under 50% RAD scenarios for both representative concentration pathway RCPs (4.5 and 8.5). The overall wheat water productivity increased under a well‐watered irrigation regime by 16% in RCP8.5 compared with RCP4.5.

Data-driven explainable artificial intelligence models for predicting CO2 uptake in metal–organic frameworks - Mohd Azfar Shaida; Laiba Saleem; Syed Ali Waqas Ahmad; Saad Shamim Ansari; Syed Muhammad Ibrahim (Environmental Science and Pollution Research, 2026)

Panel data insights into adoption of green technology and its economic role in shaping sustainability goals - Bin Xu; Ata Al Shraah; Siao-Yun Wei; Ali Mohsin Ba Awain; Muhammad Rafiq; Shamim Akhter; Tazeem Shahbaz (Clean Technologies and Environmental Policy, 2025)

Genetic diversity in wheat landraces for agronomic traits and yellow rust resistance - Shamim Khan; Niaz Ali; Fahim Ullah Khan; Israr Ud Din; Muhammad Amjad; Israr Ahmad (Genetic Resources and Crop Evolution, 2025)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

Estimating Photosynthetically Active Euphotic Layer in Major Lakes of Kumaun Region Using Secchi Depth - Zainab Khan; Sk Ajim Ali; Mohammad Mohsin; Syed Kausar Shamim; Ekaterina Mankovskaya; Farhana Parvin; Nikhat Bano; Ateeque Ahmad; Muhammad Yousuf Jat Baloch (Water, Air, & Soil Pollution, 2023)

Gravity and electrical resistivity investigations to mark concealed seepage sources from Kanjoor Dam, Pakistan - Waqar Ali Zafar; Urooj Shakir; Rizwan Ahmed; Junaid Ahmed; Muhammad Younis Khan; Shamim Akhtar; Talat Iqbal (Arabian Journal of Geosciences, 2022)

Dihydropyrimidones: A ligands urease recognition study and mechanistic insight through in vitro and in silico approach - Farman Ali Khan; Shahbaz Shamim; Nisar Ullah; Muhammad Arif Lodhi; Khalid Mohammed Khan; Kanwal; Farman Ali; Sahib Gul Afridi; Shahnaz Perveen; Ajmal Khan (Medicinal Chemistry Research, 2021)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

Synthesis, in vitro $$α $$ α -glucosidase inhibitory activity, and in silico study of (E)-thiosemicarbazones and (E)-2-(2-(arylmethylene)hydrazinyl)-4-arylthiazole derivatives - Muhammad Ali; Khalid Mohammed Khan; Uzma Salar; Mohammed Ashraf; Muhammad Taha; Abdul Wadood; Sujhla Hamid; Muhammad Riaz; Basharat Ali; Shahbaz Shamim; Farman Ali; Shahnaz Perveen (Molecular Diversity, 2018)

Enzyme inhibitory metabolites from endophytic Penicillium citrinum isolated from Boswellia sacra - Sajid Ali; Abdul Latif Khan; Liaqat Ali; Tania Shamim Rizvi; Sumera Afzal Khan; Javid Hussain; Muhammad Hamayun; Ahmed Al-Harrasi (Archives of Microbiology, 2017)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Development of sediment load estimation models by using artificial neural networking techniques - Muhammad Hassan; M. Ali Shamim; Ali Sikandar; Imran Mehmood; Imtiaz Ahmed; Syed Zishan Ashiq; Anwar Khitab (Environmental Monitoring and Assessment, 2015)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)